2020
DOI: 10.1136/bmjopen-2019-032572
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychoactive substance use among acutely hospitalised patients in Oslo and Moscow: a cross-sectional, observational study

Abstract: ObjectivesThe use of psychoactive prescription medication is increasing in the general population. This is a cause for concern, particularly among the elderly, where physiological changes related to senescence increase the risk for adverse effects. While previous studies regarding psychoactive substance use have generally been population based, we sought to determine the frequency of such use among acutely hospitalised patients.SettingTwo emergency departments (EDs), one in Oslo and one in Moscow, admitting pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…were able to test all patients meeting the inclusion criteria through anonymisation of the tests and their results. Additionally, variability between our results and previously published studies may reflect the highly variable patterns of recreational drug use from one geographic area to another because of differences in cost, supply, legality and cultural preferences 28,29 …”
Section: Discussionmentioning
confidence: 62%
“…were able to test all patients meeting the inclusion criteria through anonymisation of the tests and their results. Additionally, variability between our results and previously published studies may reflect the highly variable patterns of recreational drug use from one geographic area to another because of differences in cost, supply, legality and cultural preferences 28,29 …”
Section: Discussionmentioning
confidence: 62%
“…Therefore, the probability for adverse events, non-adherence and drug interactions might be elevated due to the diminished metabolic efficiency for both alcohol and other substances and requires careful management among the older patients drinking in a risky manner. 35 36 Nevertheless, in our study, the prevalence of multimorbidity among the young patients (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) was high (35%). The reason for this might be that our hospital comprises patients from boroughs with low income and low life expectation rates in Norway.…”
Section: Discussionmentioning
confidence: 63%
“…Of the young multimorbid patients (18-34 years) 14.1% used illicit drugs, 14.1% used psychoactive medicinal drugs and 31.4% reported to have psychological distress. Compared with the young patients, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] among multimorbid patients aged ≥35 the prevalence of psychological distress decreased with increasing age (for those aged 35-49 years the prevalence was 30.2%; for those 50-64 years it was 26.3%; 65-79 years: 23.9% and for those >80 years it was 13.8%) while the prevalence of psychoactive medicinal drug use increased substantially with increasing age (for those aged 35-49 years the prevalence was 32.6%; for those 50-64 years it was 45.4%; 65-79 years: 43.8% and for those >80 years it was 41.2%). Illicit drugs were most prevalent among those aged Open access years (16.9%) and decreased substantially with increasing age (for those 50-64 years it was 10.7%; 65-79 years 1.3% and for those >80 years it was 0.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many efects of NPS are yet to be collected and accounted for but are often directly experienced by users/consumers; also, many NPSs actually leave the market before they are identifed, perhaps after at least one death case has been attributable to them. By studying the psychoactive substances' prevalence in hospitalised patients in Moscow and Oslo via cross-sectional/observational fashion, Gamboa et al [74] showed that many patients used at least one medicinal drug with psychoactive efects, especially opiates and benzodiazepines. Elsewhere, to understand the prevalence of NPS usage among patients undergoing drug detoxifcation, Specka et al [9] analyzed responses of 295 patients and observed that majority of the patients were multiple substance users and opiate-dependent.…”
Section: Differentiating the New Psychoactive Substances (Nps) And Th...mentioning
confidence: 99%